ISOLASI DAN IDENTIFIKASI JAMUR ENDOFIT PADA TANAMAN STROBERI (Fragaria × ananassa Duch. ‘Rosalinda’) DI DESA CANDIKUNING KABUPATEN TABANAN, BALI - Meniwati; Anak Agung Darmadi; Junita Hardini (SIMBIOSIS, 2024)
Strawberries (Fragaria × ananassa Duch.) are subtropical plants well adapted to Indonesia’s highlands. Strawberries cultivated in Candikuning Village, Tabanan Regency, Bali are Fragaria × ananassa Duch. 'Rosalinda'. The fruit is widely used because it produces bioactive compounds. Bioactive compounds can also be obtained from endophytic fungi that live in host tissues. The study aimsed to identify the genus of endophytic fungi on the leaves and petioles of strawberries and to find out the benefits of the endophytic fungi found (literature review). This study used a descriptive method, which was carried out from December 2022 to February 2023. The stages in this study were the isolation of endophytic fungi, purification, and macroscopic and microscopic identification. There were 10 isolates of endophytic fungi isolated from leaves and petioles. Nine isolates were identified Aspergillus, Cercospora, Alternaria, Geotrichum, Penicillium, Cladosporium, Cylindrocladium, Cunninghamella, and Phytophthora. One isolate was not identified (mycelia sterile). These endophytic fungi are useful as biological controllers against plant pathogens, medicinal ingredients, and insecticides. Keywords: Candikuning, endophytic fungi, identification, isolation, strawberries